Comparison of some properties of 2,3- and 3,4-dimethoxybenzoates of Cu(II), Co(II) and Nd(III) - Ferenc, Wieslawa; Czapla, Katarzyna; Sarzyński, Jan; Zwolinska, Anna (Eclética Química, 2008)
The physicochemical properties of 2,4-, and 3,4-dimethoxybenzoates of Cu(II), Co(II) and Nd(III) were studied and compared to observe the -OCH3 substituent positions in benzene ring on the character of complexes. The analysed compounds are crystalline hydrated or anhydrous salts with colours depending on the kind of central ions: blue for Cu(II), pink for Co(II) and violet for Nd(III) complexes. The carboxylate groups bind as monodentate, bidentate bridging or chelating and even tridentate ligands. Their thermal stabilities were studied in air at 293-1173K. When heated the hydrated complexes release the water molecules and form anhydrous compounds which are then decomposed to the oxides of respective metals. Their magnetic moment values were determined in the range of 76-303K. The results reveal the compounds of Nd(III) and Co(II) to be the high-spin and that of Cu(II) forms dimer. The various positions of -OCH3 groups in benzene ring influence some of physicochemical properties of analysed compounds.